2023
DOI: 10.1101/2023.11.06.565758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potassium stimulates fruit sugar accumulation by increasing carbon flow in Citrus

Kongjie Wu,
Chengxiao Hu,
Peiyu Liao
et al.

Abstract: Soluble sugar is a key factor of flavor quality in citrus. Potassium (K) is known as a quality element, which plays key roles in improving sugar accumulation and fruit quality, but the mechanisms are largely unknown. This study aims to elucidate how K improves sugar accumulation by regulating carbon flow between source and sink in Newhall navel orange (Citrus sinensis). The results demonstrated that appropriate K concentration improved fruit quality and sugar accumulations in citrus, and 1.5% of K concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Through Table (9), the statistical analysis results indicate significant differences between the mean values of available potassium among the orchards in Al-Hawidr and Khan al-Walawa, with these orchards outperforming the one in Bahriz. As for the statistical analysis results between the depths' means, it showed the superiority of the first depth over the other depths.…”
Section: Available Potassiummentioning
confidence: 98%
See 1 more Smart Citation
“…Through Table (9), the statistical analysis results indicate significant differences between the mean values of available potassium among the orchards in Al-Hawidr and Khan al-Walawa, with these orchards outperforming the one in Bahriz. As for the statistical analysis results between the depths' means, it showed the superiority of the first depth over the other depths.…”
Section: Available Potassiummentioning
confidence: 98%
“…Although Iraqi soil contains a large reservoir of potassium, it is not effectively utilized due to its slow decomposition and the limited yield that does not meet the plant's needs, especially in dense agriculture [ 8 ] . [ 9 ] found that potassium participates in many physiological processes, including regulating photosynthetic processes, improving nutrient transportation, activating carbohydrate production processes, maintaining cytoplasmic pH balance, and increasing soluble sugar accumulation in citrus fruits by facilitating nutrient transportation and carbohydrate distribution. Potassium is considered a major and essential nutrient for completing the growth process in plants.…”
Section: Introductionmentioning
confidence: 99%